HUBUNGAN ANTARA STATUS IMUNISASI, SANITASI LINGKUNGAN, DAN POLA ASUH MAKAN DENGAN KEJADIAN STUNTING PADA ANAK - ULVA NOVIANA; HENI EKAWATI; mustofa haris; Diany Yoke Savira (NHM PRESS, 2022)
Stunting is a case of chronic malnutrition whose prevalence continues to increase from year to year in Indonesia. Based on the results of a preliminary study by collecting data at the Poskesdes in Meteng Village, Omben District, Sampang Regency, it was obtained. Stunting data is 13%, normal is 55%, high is 32%. The purpose of this study was to analyze the relationship between immunization status, environmental sanitation, eating patterns and the incidence of stunting in children in Meteng Village, Omben District, Sampang Regency. The study design was analytic with a retrospective approach. The independent variables are immunization status, environmental sanitation, and eating patterns. The dependent variable is the incidence of stunting. The population is 440 respondents and the sample is 86 respondents. Using case control method by purposive sampling. The research instruments were the MCH handbook and the research questionnaire. Statistical test using spearman rank with = 0.05. This research has conducted an ethical feasibility test with No: 949/KEPK/STIKES-NHM/EC/IV/2021 The results of statistical tests with the Spearman rank test p value 0.000 < = 0.05 obtained Ho is rejected, which means that there is a relationship between immunization status, environmental sanitation and parenting eating patterns with stunting in children. The results of the three variables have a relationship with the value of r = 0.585, 0.585, 0327.Through the results of this study, it can be used as a reference or source in providing health education materials or counseling to parents or people who have toddlers to prevent stunting.